2014
DOI: 10.3171/2014.5.spine13923
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of a simulated T-9 burst fracture of the thoracic spine with an intact rib cage

Abstract: Object Classic biomechanical models have used thoracic spines disarticulated from the rib cage, but the biomechanical influence of the rib cage on fracture biomechanics has not been investigated. The well-accepted construct for stabilizing midthoracic fractures is posterior instrumentation 3 levels above and 2 levels below the injury. Short-segment fixation failure in thoracolumbar burst fractures has led to kyphosis and implant failure when anterior column support i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…Because of the importance of the rib cage, several recent studies examining basic and clinical biomechanics in the human cadaveric thoracic spine have left the rib cage intact during testing (Healy et al, 2015; Mannen et al, 2015a; Perry et al, 2014). However, these studies did not include a physiological level of spinal compressive loading.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the importance of the rib cage, several recent studies examining basic and clinical biomechanics in the human cadaveric thoracic spine have left the rib cage intact during testing (Healy et al, 2015; Mannen et al, 2015a; Perry et al, 2014). However, these studies did not include a physiological level of spinal compressive loading.…”
Section: Introductionmentioning
confidence: 99%
“…From a biomechanical view, long-segment instrumentations extending at least two levels above and below the fractured vertebra are significantly more effective in immobilising the involved segment than short-segment constructs [26,27]. Thus, long-segment instrumentations of the thoracic spine achieve a 90 % reduction of extension/flexion [27]. However, more recent finite element analysis shows that short-segment stabilisation may well be sufficient for physiological loading [28].…”
Section: Fusion Lengthmentioning
confidence: 99%
“…On the whole, however, there is little available literature dealing with the question of whether short-segment management using index screws for the middle and upper thoracic spine is adequate enough. Given the proven reduction of biomechanical stability, short-segment management has no place in the treatment of highly unstable type A4 fractures and type B and C fractures, especially those associated with injury to the bony ribcage [26,27]. In addition, it should be kept in mind that, on the one hand, clinical studies have shown an increased tendency for recurrent kyphotic deformity following short-segment management and, on the other hand, no functional difference has been demonstrated between long-segment and short-segment management [20,29].…”
Section: Associated Injuriesmentioning
confidence: 99%
“…In general, the structural instability of thoracic fractures is treated with posterior instrumentation 2 levels above and below the fracture site, but in case of intact rib cage a short segment fixation with 1 level above and below the fractured vertebra could be an alternative. Therefore, Perry et al [30] created a burst fracture at T9 in eight human thoracic spines (C7-L1) with intact rib cages and tested a long segment instrumentation (3 above, 2 below), a short segment instrumentation (1 above/1 below) with and without vertebral augmentation and vertebral augmentation without instrumentation. In their study, the long segment instrumentation showed a significant reduction of ROM during flexion-extension (− 90%), whereas the other instrumentations only tended to reduce motion.…”
Section: Biomechanicsmentioning
confidence: 99%
“…In their study, the long segment instrumentation showed a significant reduction of ROM during flexion-extension (− 90%), whereas the other instrumentations only tended to reduce motion. However, Perry et al [30] suggested that in case of intact rib cages short segment instrumentation might adequately stabilize the spine. A common strategy to increase stability of short segment fixation is the addition of cross-links or screws at fracture site (index screws).…”
Section: Biomechanicsmentioning
confidence: 99%